Body Mass Index Trajectories and Healthcare Utilization in Young and Middle-aged Adults. Issue 2 (January 2016) - Elrashidi, Muhamad Y.; Jacobson, Debra J.; St. Sauver, Jennifer; Fan, Chun; Lynch, Brian A.; Rutten, Lila J. Finney; Ebbert, Jon O.
Abstract : Abstract: The obesity epidemic is a significant public health issue with adverse impact on health and costs. Applying a life-course perspective to obesity may advance our understanding of the influence of obesity over time on patterns of healthcare utilization in young and middle-aged United States (US) adults. We identified baseline body mass index (BMI) and BMI trajectories, and assessed their association with outpatient visits, emergency department (ED) visits, and hospitalizations in a well-defined population of young and middle-aged US adults. Using the Rochester Epidemiology Project resources, we conducted a retrospective cohort study of adults (N = 23, 254) aged 18 to 44 years, with at least 3 BMI measurements, residing in Olmsted County, MN from January 1, 2005 through December 31, 2012. We observed that 27.5% of the population was obese. Four BMI trajectories were identified. Compared to under/normal weight, obese class III adults had higher risk of outpatient visits (adjusted rate ratio [RR], 1.86; 95% confidence intervals [CIs], 1.67–2, 08), ED visits (adjusted RR, 3.02; 95% CI, 2.74–3.34), and hospitalizations (adjusted RR, 1.67; 95% CI, 1.59–1.75). BMI trajectory was positively associated with ED visits after adjustment for age, sex, race, and Charlson Comorbidity Index ( P  < 0.001 for trend). Among young and middle-aged US adults, baseline BMI is positively associated with outpatient visits, ED visits, and hospitalizations, while BMI trajectory is positively associated with ED visits. These findings extend our understanding of the longitudinal influence of obesity on healthcare utilization in early to mid-adulthood.